The Professional Role of Teachers in Integrating Interactive Media in English Language Learning in Schools - Audina, Mia; Zulfah, Zulfah; Sunubi, Abdul; Mujahidah, Mujahidah; Tjalla, Magdahalena (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2025)
This study aims to describe the level of English teachers' professionalism in integrating interactive media in learning and to identify the factors that influence its implementation in schools. A descriptive quantitative approach was employed, involving a sample of 50 English teachers from various education levels. The research instrument consisted of a Likert-scale questionnaire that measured aspects of teacher professionalism, frequency of interactive media use, and supporting or inhibiting factors. The results showed that the overall mean score for teacher professionalism was 3.65 with a standard deviation of 0.90. The highest score was found in the student engagement indicator (mean = 3.80; SD = 0.97), and the lowest was in the frequency of media use (mean = 3.42; SD = 0.86). Regarding factors influencing media use, the highest mean scores were in perceived learning effectiveness (mean = 4.28; SD = 0.78), student interest (mean = 4.24; SD = 0.87), and teachers' motivation for self-development (mean = 4.20; SD = 0.95). Meanwhile, training support from schools showed the lowest score (mean = 3.98; SD = 1.06), indicating the need for stronger institutional support. In conclusion, while teachers show a positive attitude toward interactive media, its optimal integration is still limited by training, facilities, and time management constraints.‎   Keywords:‎ Teacher Professionalism, Interactive Media, English Language Learning